Silage production and the chemical composition of corn and Grass-tanzania intercropping - Fabiana Luiza Matielo de Paula; Luis Fernando Glasenapp de Menezes; Wagner Paris; Ricardo Ronsani; Sarah Maria Hoppen; Julio Ciesca (Semina: Ciências Agrárias, 2016)
The objective of this study was to evaluate the production and chemical composition of silages of grass Tanzania and corn, grown single or intercropping. The experiment was conducted at UTFPR Câmpus Dois Vizinhos in the period between October 2011 and July 2012, a 600 m² area. The treatments were: TMI - single corn, TMT - corn and grass Tanzania consortium at the time of sowing, TT - Tanzania grass single, TT32 - grass Tanzania silage to 32% dry matter (content similar to that of corn). The experimental design a randomized block design with four treatments and five replications. Agronomic evaluations were performed 120 days after planting, as follows: number of linear-1 plants metro, plant height and ear insertion and number of ears.plants-1. In the grass we evaluated canopy height, where it was held the botanical separation in green leaves, dried and stem. Silage started being held in 100 mm PVC pipe (mini-silos) kept sealed for 60 days. At the time of opening of the silo were determined the following parameters: DM, pH, total loss of DM (PDM), specifies mass (SM), dry matter recovery indices (IRDM), losses gas (LG), and size particle. Chemical analysis of the results of OM, MM, ADF were higher for TMI treatments, TT and TT, respectively. CP and LIG had superior results for the treatments containing grass. Corn intercropping with grass Tanzania silage provides more crude protein and lignin compared to exclusive corn silage without damaging the crop yield. Silage maiden Tanzania has higher levels of ADF and crude protein as well as increased production of dry matter than corn silage. The grass Tanzania should be harvested with 30% DM as presented better pH values, higher dry matter recovery rate, less loss of gas as well as increased production of dry matter that Tanzania harvested at the same age corn.